2006
DOI: 10.1021/jm051144x
|View full text |Cite
|
Sign up to set email alerts
|

A Pyridazine Series of α2/α3 Subtype Selective GABAA Agonists for the Treatment of Anxiety

Abstract: The development of a series of GABA(A) alpha2/alpha3 subtype selective pyridazine based benzodiazepine site agonists as anxiolytic agents with reduced sedative/ataxic potential is described, including the discovery of 16, a remarkably alpha3-selective compound ideal for in vivo study. These ligands are antagonists at the alpha1 subtype, with good CNS penetration and receptor occupancy, and excellent oral bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…9); or a3bg2 selectivity (compound 16). These ligands exhibit no modulatory activity at the a1 subtype, a good central nervous system penetration and receptor occupancy, and excellent oral bioavailability (Lewis et al, 2006). To the best of our knowledge, no additional studies have been reported on these compounds.…”
Section: Compounds Claimed To Selectively Modulate A2bg2 and A3bg2mentioning
confidence: 99%
“…9); or a3bg2 selectivity (compound 16). These ligands exhibit no modulatory activity at the a1 subtype, a good central nervous system penetration and receptor occupancy, and excellent oral bioavailability (Lewis et al, 2006). To the best of our knowledge, no additional studies have been reported on these compounds.…”
Section: Compounds Claimed To Selectively Modulate A2bg2 and A3bg2mentioning
confidence: 99%
“…It is generally accepted that the beneficial anxiolytic, myorelaxant, and cognitive effects of BDZs are mediated by α2 and α3 containing channels, whereas the undesirable sedative and dependence actions are α1 mediated. [7][8][9][10] There have been widespread and extensive searches for improved, subtype-selective drugs for GABA channels, but these have been hampered by the availability of suitable highthroughput screening (HTS) and secondary hit confirmation approaches (for review, see Smith and Simpson 11 ). Radioligand binding assays (e.g., 3 H flunitrazepam, 3 H muscimol) have proven useful but cannot differentiate agonism/ antagonism or positive/negative modulation and, with the multitude of recognition sites, fail to provide the full picture.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This suggested that, rather than employing anhydrous KF, it would be preferable to use the commercially available dihydrate (KF•2H 2 O; entry 2 vs. entry 6). In addition to restoring the efficiency of the Pd/P(t-Bu) 3 -catalyzed Suzuki cross-coupling, this modification has the added advantage of a very substantial cost savings (price per mole: anhydrous KF ($450/ mol); KF•2H 2 O ($19/mol)).…”
Section: Resultsmentioning
confidence: 99%